Creatine supplementation and upper limb strength performance: A systematic review and meta-analysis - Lanhers, C.; Pereira, B.; Naughton, G.; Trousselard, M.; Lesage, F.-X.; Dutheil, F. (Sports Medicine, 2017)
Background: Creatine is the most widely used supplementation to increase performance in strength; however, the most recent meta-analysis focused specifically on supplementation responses in muscles of the lower limbs without regard to upper limbs. Objective: We aimed to systematically review the effect of creatine supplementation on upper limb strength performance. Methods: We conducted a systematic review and meta-analyses of all randomized controlled trials comparing creatine supplementation with a placebo, with strength performance measured in exercises shorter than 3 min in duration. The search strategy used the keywords `creatine`, `supplementation`, and `performance`. Independent variables were age, sex and level of physical activity at baseline, while dependent variables were creatine loading, total dose, duration, time interval between baseline (T0) and the end of the supplementation (T1), and any training during supplementation. We conducted three meta-analyses: at T0 and T1, and on changes between T0 and T1. Each meta-analysis was stratified within upper limb muscle groups. Results: We included 53 studies (563 individuals in the creatine supplementation group and 575 controls). Results did not differ at T0, while, at T1, the effect size (ES) for bench press and chest press were 0.265 (95 % CI 0.132-0.398; p < 0.001) and 0.677 (95 % CI 0.149-1.206; p = 0.012), respectively. Overall, pectoral ES was 0.289 (95 % CI 0.160-0.419; p = 0.000), and global upper limb ES was 0.317 (95 % CI 0.185-0.449; p < 0.001). Meta-analysis of changes between T0 and T1 gave similar results. The meta-regression showed no link with characteristics of population or supplementation, demonstrating the efficacy of creatine independently of all listed conditions. Conclusion: Creatine supplementation is effective in upper limb strength performance for exercise with a duration of less than 3 min, independent of population characteristics, training protocols, and supplementary doses or duration.